CONTROL ALGORITHM AIRCRAFT UNDER SUDDEN STEERING SURFACE DAMAGE - Казак, В. М.; Будзинська, Т. В.; Міщерякова, В. Ю. (Science-based technologies, 2009)
An analysis of damage influenece on control surfaces was made. The mathematic model of such influence and methods of aircraft’s controllability resumption were developed.